1728 Are we Following the Rcpch Guidelines for Clinic Letters? an Audit. (October 2012) - Damodaran, S; Abraham, D; Erumbala, G; Doddamani, L
Abstract : Introduction: This is an audit of letters done by various professionals in community paediatric clinic in a district hospital. Methods: Two letters each were selected from all Consultant and Associate Specialist clinics, nurse led enuresis clinic and nurse led constipation clinic. There were a total of 14 letters. These were compared with the Sheffield Assessment Instrument for Letters (SAIL) which is the standard suggested by RCPCH. Results: There was 100% compliance with standard requirement in 14 areas of RCPCH standard. The main deficiency was in writing drug dosages; only 57% letters have doses mentioned. Interestingly, more than one third of letters did not have a problem list. In 21.5% of letters, the documented examination was not appropriate to the problems and questions. Conclusion: After discussion in the departmental audit meeting, the following recommendations were made SAIL checklist to be circulated among team members so that all are aware of the standards suggested by RCPCH. A reaudit was planned after 6 months to check compliance.